The Impact of Infectious Diseases on Kenya’s Health Diplomacy; An Inter-State Phenomenon - Kurgat, Paul K.; Kurgat, Alice J.; Juma, Thomas Otieno (Archives of Business Research, 2020)
The impact of infectious diseases is a real global phenomenon in the 21st century buoyed by the accelerated pace of globalization which seem to dissolve the distinctions between; many domestic and foreign issues, regions and multinational actors, and even friendly and hostile states. The impact of infectious diseases on Kenya’s health diplomacy calls for need to enhance public health partnerships to tackle such issues of international concern to effectively handle such diplomacy matters and timely. The study used qualitative study methodology by describing the context of Kenya’s health diplomacy and employing available documents analysis. The study concluded that controlling emerging and reemerging infectious diseases require extreme actions and coordination between many national and international actors which Kenya and her international network of states must do through diplomacy.